Analisis Hukum Terhadap Pertanggungjawaban Tipikor Dana LPD Pada Seksi Tindak Pidana Khusus di Kejaksaan Negeri Karangasem - Ni Putu Desi; Nurianto Rachmad Soepadmo; Ida Bagus Anggapurana Pidada (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2024)
LPD is an institution in the financial services sector whose main activity is accepting deposits/savings and also deposits from the traditional village krame itself. In its management, LPD also functions as a place to borrow money or credit with conditions that are much lighter than other banking institutions but are intended for only specific to their own traditional village manners. In cases of criminal acts of corruption that have occurred so far, not only are they detrimental to state finances, but are also violations of the social and economic rights of society at large, so that criminal acts of corruption need to be classified as crimes whose eradication must be carried out in an extraordinary manner. Law enforcement agencies, such as the Corruption Eradication Committee, the police and the prosecutor's office, must always be alert in the process of investigating and handling corruption cases which are very widespread in Indonesia. Apart from that, to further guarantee legal certainty, avoid variations in legal interpretation and provide protection for the social and economic rights of the community, as well as fair treatment for members of criminal acts of corruption, it is necessary to make changes to Law Number 31 of 1999 concerning the Eradication of Criminal Acts. Corruption.